Electric Scooter with Efficient Power Monitoring and Extended Distance - Azhar, Mohammad Azzam (Universiti Teknologi PETRONAS, 2017)
Electric scooter is one of the popular options of vehicle nowadays, it is either comes in as Hybrid Electric Vehicle (HEV) or Battery Electric Vehicle (BEV). The distance for the electric scooter could travelled does not reach users’ expectation compared to normal petrol powered scooter is one of the reasons why people choose to have normal petrol powered electric scooter instead of electric scooter. Electric scooters are always equipped with an indicator or known as Battery Monitoring System (BMS) for the user to check on the battery conditions which is not really accurate as the battery behaviour is a complex electrochemical component. BMS functions as a component to determine the battery level, speed as well as the distance range.